2020
DOI: 10.1038/s41598-020-77863-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of grain boundary premelting

Abstract: The mechanical strength of a polycrystalline material can be drastically weakened by a phenomenon known as grain boundary (GB) premelting that takes place, owing to the so-called disjoining potential, when the dry GB free energy $$\sigma _{gb}$$ σ gb exceeds twice the free energy of the solid–liquid interface $$\sigma _{sl}$$ σ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…melting point. This order-disorder transition is termed GB premelting (Torabi Rad et al, 2020) and has been observed in many materials (e.g., Glicksman & Vold, 1972;Dillon & Harmer, 2007;Frolov et al, 2013). Similar to the findings of Riet, Van Orman, and Lacks (2021) and , the GB in this quasi-liquid state exhibits considerable disorder nature and transport properties close to those of a supercooled liquid.…”
Section: Open Researchsupporting
confidence: 76%
“…melting point. This order-disorder transition is termed GB premelting (Torabi Rad et al, 2020) and has been observed in many materials (e.g., Glicksman & Vold, 1972;Dillon & Harmer, 2007;Frolov et al, 2013). Similar to the findings of Riet, Van Orman, and Lacks (2021) and , the GB in this quasi-liquid state exhibits considerable disorder nature and transport properties close to those of a supercooled liquid.…”
Section: Open Researchsupporting
confidence: 76%
“…Good results have been obtained compared to previous experiments on temperaturedependent molten surface layer thickness for nanoparticles and size-dependent melting temperature [42,43]. The PFM is used for modeling the premelting of grain boundaries in pure materials [44][45][46]. Crystal-crystal PT is modeled via the PFM as a surface-induced virtual premelting [47].…”
Section: Introductionmentioning
confidence: 66%
“…The GB activation energies at high temperatures fall in the range of 0.2 to 0.4 eV, suggesting a different diffusion mechanism compared to low temperature diffusion. Prior studies 17,57–59 have reported that pre-melting can occur at GBs – i.e. , a disordered phase forms in the GB region at temperatures below the bulk melting temperature.…”
Section: Resultsmentioning
confidence: 99%